Spinal Cord Ependymoma Presenting as Recurrent Pain Abdomen in a Child with Post-operative Follow UP - Sharma, Shashi; Sharma, Bharat Bhushan; Rao, Dashrath; Bhutani , Abhivind; Batra, Chakshu; Sarin , Monu; Kapur , Neeru; Nargotra , Natasha; Chugh, Nalin; Arora, Naresh Chander (New Horizons in Medicine and Medical Research Vol. 9, 2022)
In the paediatric age group, spinal cord ependymomas are the second most prevalent tumor of the spinal cord. These are intramedullary tumors that must be discovered as soon as possible to prevent neurological consequences. The epidemiology and overall survival characteristics are the most essential considerations. We present a 14-year-old boy who was assessed for an eight-month history of persistent abdominal pain. Ultrasonography, barium tests, upper gastro-intestinal tract (GIT) endoscopy, contrast enhanced computerized tomography (CECT) abdomen, and magnetic resonance imaging (MRI) were all performed on him. He had a nerve sheath tumor of the distal spinal cord, according to his preliminary diagnosis. The tumor was surgically removed, and it was discovered to be an ependymoma. The child had recurrent abdominal pain and was treated for several conditions, but tests revealed the underlying pathology as a spinal cord tumor. Cross-sectional imaging, such as MRI, is the only way to detect these tumors.